Characteristics of Male Bali Cattle in Toili District - Laya, Nibras K.; Arifin, Muhammad A.; Syahruddin, syahruddin; Fathan, Suparmin; Datau, Fahria; Gubali, Syukri I.; Dako, Safriyanto (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2024)
Bali cattle family is one of four native Indonesian cattle breeds that play an important role as a domestic source of meat. Bali cattle have a major problem in their development such as low quality breeds due to inbreeding (internal crossbreeding) or maintenance management. One of the efforts to improve genetic quality and increase cattle productivity sustainably is through Performance testing. The aim of this research was to determine the phenotypic performance of male Bali cattle on community farms in Banggai Regency. The research used 100 male Bali cattle aged 2-3 years. This research used a field experimental method through observing and measuring livestock. The data was analyzed descriptively, describing the facts at the research location. The result show that body hair color of male Bali cattle consisted of brown, dark brown, blackish brown and black. The boundaries of the body color pattern on the legs and buttocks mirror were clearly visible, without any changes or deviations. Body weight of Bali cattle was 204.56 ± 14.32 kg. Body weight was strongly correlated with chest circumference, body length and height